2001
DOI: 10.1109/20.950846
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of perpendicular recording heads

Abstract: Abstract-3D modeling and inductance measurements were used to design an ultra-high frequency perpendicular system. Kerr microscopy and spin-stand experiments with focused ion beam (FIB) trimmed perpendicular heads and perpendicular media directly verified the high frequency concepts.Index Terms-Focused ion beam (FIB), next generation magnetic recording systems, perpendicular recording dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The influence of a SUL on the dynamic characteristics of a recording system remains one of the open questions pertinent to the development of the technology. A detailed study of the SPH/SUL dynamics can be found in [7]. The present paper extends the analysis to include the influence of a recording layer on the SUL dynamic properties.…”
Section: Introductionmentioning
confidence: 96%
“…The influence of a SUL on the dynamic characteristics of a recording system remains one of the open questions pertinent to the development of the technology. A detailed study of the SPH/SUL dynamics can be found in [7]. The present paper extends the analysis to include the influence of a recording layer on the SUL dynamic properties.…”
Section: Introductionmentioning
confidence: 96%
“…The relative exchange coupling constant, he, was modeled to be anisotropic: with the in-plane and perpendicular-to-the-plane exchange constants equal to 0.05 and 0.5 for Co-based "single" layer, respectively, and 0.1 and 0.5 for Co/Pt-based "single layer, respectively. Figure 3c illustrates a micromagnetically simulated magnetization pattern [6] after applying the recording field from a single pole head to a stack of multilayers with an interlayer separation (Pt layer thickness) of less than one nanometer. The field from the single pole head was also modeled micromagnetically.…”
Section: Preliminary Numerical Simulations Of 3-d Mediamentioning
confidence: 99%